Characterizing multi‐word speech production using event‐related potentials. (10th February 2021) - Ries, Stephanie K.; Pinet, Svetlana; Nozari, N. Bonnie; Knight, Robert T.
Abstract: Event‐related potentials (ERPs) derived from electroencephalography (EEG) have proven useful for understanding linguistic processes during language perception and production. Words are commonly produced in sequences, yet most ERP studies have used single‐word experimental designs. Single‐word designs reduce potential ERP overlap in word sequence production. However, word sequence production engages brain mechanisms in different ways than single word production. In particular, speech monitoring and planning mechanisms are more engaged than for single words since several words must be produced in a short period of time. This study evaluates the feasibility of recording ERP components in the context of word sequence production, and whether separate components could be isolated for each word. Scalp EEG data were acquired, while participants recited word sequences from memory at a regular pace, using a tongue‐twister paradigm. The results revealed fronto‐central error‐related negativity, previously associated with speech monitoring, which could be distinguished for each word. Its peak amplitude was sensitive to Cycle and Phonological Similarity. However, an effect of sequential production was also observable on baseline measures, indicating baseline shifts throughout the word sequence due to concurrent sustained medial‐frontal EEG activity. We also report a late left anterior negativity (LLAN), associated with verbal response planning and execution, onsetting around 100 ms before the first word in each cycle and sustained throughout the rest of the cycle. This work underlines the importance of considering the contribution of transient and sustained EEG activity on ERPs, and provides evidence that ERPs can be used to study sequential word production. Abstract : Words are commonly produced in sentences, yet most ERP studies have used single‐word experimental designs. This study establishes the feasibility of recording ERP components in the context of word sequence production and underlines the importance of considering the contribution of transient and sustained EEG activity on ERPs while we speak.